2016
DOI: 10.4155/fmc-2016-0071
|View full text |Cite
|
Sign up to set email alerts
|

H3K36 Methyltransferases as Cancer Drug Targets: Rationale and Perspectives for Inhibitor Development

Abstract: Methylation at histone 3, lysine 36 (H3K36) is a conserved epigenetic mark regulating gene transcription, alternative splicing and DNA repair. Genes encoding H3K36 methyltransferases (KMTases) are commonly overexpressed, mutated or involved in chromosomal translocations in cancer. Molecular biology studies have demonstrated that H3K36 KMTases regulate oncogenic transcriptional programs. Structural studies of the catalytic SET domain of H3K36 KMTases have revealed intriguing opportunities for design of small mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 149 publications
(232 reference statements)
1
30
0
Order By: Relevance
“…NSD1, MMSET, WHSC1L1, ASH1L, and SETD2 have closely related catalytic SET domains and show H3K36 methylation specificity in vitro and in vivo, while SMYD2, SETMAR, and SETD3 have less similarity in their SET domains with less well-characterized activities toward H3K36. 203 For example, SMYD2 (also known as KMT3C) was reported to methylate H3K4 as well as H3K36 in vitro, 152 and SMYD2-mediated H3K36me2 was reported to repress the transcription of pro-inflammatory cytokines IL-6 and TNF-α in macrophages. 204 However, inhibition or knockdown of SMYD2 does not affect global levels of mono-, di-, or trimethylation of H3K4 or H3K36, and most of SMYD2 is found in the cytoplasm, suggesting minimal SMYD2 activity on chromatin.…”
Section: Protein Methyltransferasesmentioning
confidence: 99%
“…NSD1, MMSET, WHSC1L1, ASH1L, and SETD2 have closely related catalytic SET domains and show H3K36 methylation specificity in vitro and in vivo, while SMYD2, SETMAR, and SETD3 have less similarity in their SET domains with less well-characterized activities toward H3K36. 203 For example, SMYD2 (also known as KMT3C) was reported to methylate H3K4 as well as H3K36 in vitro, 152 and SMYD2-mediated H3K36me2 was reported to repress the transcription of pro-inflammatory cytokines IL-6 and TNF-α in macrophages. 204 However, inhibition or knockdown of SMYD2 does not affect global levels of mono-, di-, or trimethylation of H3K4 or H3K36, and most of SMYD2 is found in the cytoplasm, suggesting minimal SMYD2 activity on chromatin.…”
Section: Protein Methyltransferasesmentioning
confidence: 99%
“…In addition, mono‐methylation of H3K9, H3K27, and H3K79 and dimethylation of H3K79 are gene transcription activator, while trimethylation of H3K79 is facultive . Also, H3K4 me3 and H3K4 me2 marks are known to bind directly to transcriptional activators and also H3K36 methyltransferases are considered as cancer drug targets …”
Section: Introductionmentioning
confidence: 99%
“…31,32 Also, H3K4 me3 and H3K4 me2 marks are known to bind directly to transcriptional activators 33,34 and also H3K36 methyltransferases are considered as cancer drug targets. 32,35 Emerging evidences revealed that small ubiquitinlike modifiers (SUMOs) such as SUMO-1, SUMO-2, and SUMO-3 in mammalian systems 36 are found covalently attached to more than 50 proteins including p53, androgen receptor, IkBα, c-jun, histone deacetylases (HDACs), and other proteins 37 with major functions of SUMOylation, cytoplasmic nuclear transport, transcripton, and DNA repair. 38 Although paclitaxel, so-called taxol, has been used for chemotherapy in several cancers including ovarian cancer, breast cancer, lung cancer, Kaposi sarcoma, cervical cancer, and pancreatic cancer and cancer stem cells, 39 its resistance in stem cells 40,41 and side effects 42,43 are still hot issues for effective cancer therapy.…”
mentioning
confidence: 99%
“…Histone lysine methylation was regarded as a central modification for the post-transcriptional regulation of chromosome structure and DNA replication, repair, and transcription procedure [14], and was relevant to the activation or silencing of gene expression [15]. KDM2A can specifically catalyze the demethylation of histone H3K36, which is a conserved epigenetic marker influencing gene transcription, alternative splicing, and DNA repair [16,17]. During cell mitosis, KDM2A plays a role in maintaining genomic stability and centromeric integrity [11].…”
Section: Discussionmentioning
confidence: 99%